Comparison of PERPRO tools grade N5 and N10 against grade N5D and N10D - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
Tools of grade N5, N5D, N10 and N1OD were tested to 0.030 in. flankwear when machining EN 9 at a cutting speed of 500 f.p.m. with 0.010 in/rev. feed and 0.10 in. depth of cut. The results showed that there was no significant difference in tool life between the normal grades and the 'D’ grades.